An instruction-level energy model for embedded VLIW architectures. - Sami, M.
In this paper, an instruction-level energy model is proposed for the data-path of very long instruction word (VLIW) pipelined processors that can be used to provide accurate power consumption information during either an instruction-level simulation or power-oriented scheduling at compile time. The analytical model takes into account several software-level parameters (such as instruction ordering, pipeline stall probability, and instruction cache miss probability) as well as microarchitectural-level ones (such as pipeline stage power consumption per instruction) providing an efficient pipeline-aware instruction-level power estimation, whose accuracy is very close to those given by RT or gate-level simulations. The problem of instruction-level power characterization of a K-issue VLIW processor is O(N2K) where N is the number of operations in the ISA and K is the number of parallel instructions composing the very long instruction. One of the advantages of the proposed model consists of reducing the complexity of the characterization problem to O(K×N 2). The proposed model has been used to characterize a four-issue VLIW core with a six-stage pipeline
Keywords: VLIW; Embedded architectures; Four-issue core; Instruction cache miss probability; Instruction ordering; Instruction-level energy model; Instruction-level simulation; Pipeline stall probability; Pipelined processors; Power consumption information; Power-oriented scheduling; Six-stage pipeline; Software-level parameters; Very long instruction